The progenitor mass of the Type IIP supernova SN 2004et from late-time spectral modeling - Jerkstrand, A; Fransson, C; Maguire, K; Smartt, S; Ergon, M; Spyromilio, J (2012)
SN 2004et is one of the nearest and best-observed Type IIP supernovae, with a progenitor detection as well as good photometric and spectroscopic observational coverage well into the nebular phase. Based on nucleosynthesis from stellar evolution/explosion models we apply spectral modeling to analyze its 140-700 day evolution from ultraviolet to mid-infrared. We find a M ZAMS = 15 M âŠ(tm) progenitor star (with an oxygen mass of 0.8 M âŠ(tm)) to satisfactorily reproduce [Oâ‰i] λλ6300, 6364 and other emission lines of carbon, sodium, magnesium, and silicon, while 12 M âŠ(tm) and 19 M âŠ(tm) models under-and overproduce most of these lines, respectively. This result is in fair agreement with the mass derived from the progenitor detection, but in disagreement with hydrodynamical modeling of the early-time light curve. From modeling of the mid-infrared iron-group emission lines, we determine the density of the "Ni-bubble" to ρ(t) â‰7 × 10 -14 × (t/100 d) -3 g cm -3, corresponding to a filling factor of f = 0.15 in the metal core region (V = 1800 kmâ‰ s -1). We also confirm that silicate dust, CO, and SiO emission are all present in the spectra. ©2012 ESO.